The Role of Emotion in Ethical Decisionmaking - Callahan, Sidney (The Hastings Center report, 1988)
In the rationalist tradition in ethics, the emotions are morally suspect. In a corrective swing of the pendulum, burgeoning philosophical interest is “rehabilitating” the emotions in ethical decisionmaking. The emotions and reason should be mutually correcting resources in moral reflection.